Differences in cardiovascular responses to supine exercise and to standing after exercise in two clinical subgroups of Shy-Drager syndrome (multiple system atrophy). Issue 3 (September 1996) - Smith, G D; Mathias, C J
Abstract : BACKGROUND: In chronic autonomic failure of varying aetiologies, there are differences in the cardiovascular responses to supine leg exercise and to standing after exercise. Whether this occurs between the different subgroups with Shy-Drager syndrome (SDS) is unknown. METHODS: Fourteen patients with the cerebellar form (SDS-C) and 11 patients with parkinsonian features (SDS-P) were studied. RESULTS: Both groups had a similar degree of autonomic failure and postural hypotension. Their responses were compared with nine patients with idiopathic Parkinson's disease (IPD) and 15 normal subjects (controls), all with normal autonomic function. With supine exercise, blood pressure and heart rate rose similarly in controls and patients with IPD and there was no fall in blood pressure on standing after exercise. In both SDS groups there were abnormal responses to exercise: blood pressure fell in SDS-C, but did not fall or rise in SDS-P. Heart rate increased similarly in both SDS groups, calculated systemic vascular resistance fell similarly, but cardiac index rose more in SDS-P than SDS-C. Resting plasma noradrenaline concentrations were subnormal in both forms of SDS, and did not increase with exercise. Postural hypotension was enhanced after exercise to the same extent in SDS-C and SDS-P. CONCLUSIONS: The greater cardiovascular abnormalities in response to exercise in SDS-C suggests that cerebellar or brain stem autonomic pathways are impaired to a greater extent in SDS-C than in SDS-P. Pooling SDS subgroups, therefore, may obscure pathophysiological differences to certain stimuli. Clinically when postural hypotension is being assessed, separation of the subgroups may not be essential, as they responded similarly.